Dry heat treatment of skim milk powder greatly improves the heat stability of recombined evaporated milk emulsions. (March 2021) - Wu, Jianfeng; Chen, Simin; Sedaghat Doost, Ali; A'yun, Qurrotul; Van der Meeren, Paul
Abstract: In this study, skim milk powder (SMP) was subjected to a controlled dry heat treatment at 60 °C and relative humidity of 74% to improve the heat stability of recombined evaporated milk (REM) emulsions. Free amino group determination and SDS-PAGE analysis confirmed that the glycation of both whey proteins (WP) and caseins with lactose mainly occurred in the early period (<8 h). An increase in surface hydrophobicity and changes in the structure of the SMP proteins by circular dichroism (CD) and FT-IR were found after a long time of incubation (>16 h). The non-sedimentable protein analysis indicated that WP-casein interaction and casein micelle dissociation happened during (prolonged) dry heating. The heat stability of REM emulsions stabilized by dry-heated SMP was greatly improved: dry-heated SMP-stabilized REM emulsions could withstand at least 30 min of heating at 120 °C without significant increase in particle size and viscosity ( P > 0.05 ). However, excessive dry heating (>20 h) adversely affected the reconstitution ability of SMP as well as the heat stability of REM emulsions. Graphical abstract: Image 1 Highlights: Dry heating of SMP gave rise to the formation of conjugates of milk proteins and lactose. SDS-PAGE analysis proved glycation of both whey proteins and caseins (in micellar state). The heat stability of REM stabilized by dry-heated SMP was largely improved as compared to native SMP stabilized REM. Dry-heated SMP-stabilized REM emulsions could withstand at least 30min of heating at 120 °C without coagulation. Excessive dry heating (>20 h) adversely affected the reconstitution ability of SMP as well as the heat stability of REM.